Father’s positive parenting and his beliefs about the role of the father in a Portuguese sample - Amaral, R.; Monteiro, L.; Santos, C. (26th ISSBD Biennial Meeting of the International Society for the Study of Behavioural Development (Conference canceled), 2020)
In Portugal, changes towards a “new generation” of fathers who perceive their roles in work and family to be equally important seems to be a trend (Wall et al., 2016). These beliefs are expressed though their parenting styles and practices having impact, to some extent, in the quality of parent/child relationship (Darling & Steinberg, 1993). Thus, it is expected that traditional versus progressive beliefs may have a different impact in parenting behaviors and practices adopted by fathers (Grusec & Danyliuk, 2014). The present study aimed to analyze the relations between father’s beliefs about the role of the father and the quality of parenting (positive and negative), testing the moderating role of education. Method: Participants were 215 fathers, married, with children attending pre-school and employed full time. Fathers completed The Role of the Father (Palkovitz, 1984) and the Parenting Styles and Dimensions Questionnaire (Robinson et al., 2001). Results show a positive and significant association between father’s beliefs and Positive Parenting (r(215)=.30, p =.00), and a negative and significant association between his beliefs and Negative Parenting (r(215)=-.17, p=.01). A positive and significant association between father’s education (r(214)=.14, p=.03) and Positive Parenting was also found. Multiple hierarchical regression models were conducted. The Negative Parenting model did not reach statistical significance. For Positive Parenting (F(7, 202)=5.84; p= .00; R2a= .14), father’s beliefs (b = .33, p = .00) were a significant predictor. An interaction effect between father’s beliefs and education was also found (? = -.08, p = .00), suggesting that those who have lower and medium levels of education, have a more positive parenting, when their beliefs are progressive. Results will be discussed in terms of the importance of considering the way fathers perceive their roles, but also of education, when delineating programs aiming to promote their positive involvement, well-being, and parenting skills.